Indoor experimental study on the remediation of petroleum hydrocarbon-contaminated groundwater by microbial PRB technology - LU Gang; HUO Xinyi; XU Handong; LU Shilei; JIANG Shuai; YU Shuangfei (Gongye shui chuli)
With the extensive use of petroleum and petroleum products, petroleum hydrocarbon pollution in groundwater becomes serious. In-situ permeable reactive wall(PRB) is an important means to remediate groundwater pollution. Based on the PRB simulation column experiments, biochar-immobilized petroleum hydrocarbon-degrading bacteria as the PRB reaction medium were used to explore the optimum groundwater flow rate, and the performance of the microbial PRB reaction medium was investigated. The results showed that the optimal groundwater flow rate of the microbial PRB was 6 mL/min, and the removal rates of petroleum hydrocarbons in the simulated wastewater and the polluted groundwater were 88.41% and 69.72% after 30 days, respectively. With the running of reaction, the pH of the effluent did not change significantly, while the redox potential and content of dissolved oxygen decreased. The performance evaluation of microbial PRB reaction medium during the reaction showed that the PRB reaction medium had effective degradation on straight-chain alkanes (C10-C25). The desorption of petroleum hydrocarbons precipitate from the immobilized bacteria was relatively rapid, with a desorption amount of 53.66 mg/g.